2014
DOI: 10.1002/bit.25245
|View full text |Cite
|
Sign up to set email alerts
|

Tuning single‐cell oil production in Ashbya gossypii by engineering the elongation and desaturation systems

Abstract: Microbial oils represent a sustainable alternative to vegetable oils and animal fats as feedstock for both the chemical and biofuel industries. The applications of microbial oils depend on their fatty acid composition, which is defined by the relative amount of each fatty acid, also considering the length and unsaturations of the acyl chain. These two properties are determined by elongases and desaturases. In the present study, we characterized the elongase and desaturase systems in the filamentous fungus Ashb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…Overexpression led to nervonic acid (24:1) production and disruption resulted in SCO with properties that meet some biodiesel quality standards Ledesma-Amaro et al (2014c) …”
Section: Accepted M M a N U mentioning
confidence: 99%
“…Overexpression led to nervonic acid (24:1) production and disruption resulted in SCO with properties that meet some biodiesel quality standards Ledesma-Amaro et al (2014c) …”
Section: Accepted M M a N U mentioning
confidence: 99%
“…The ΔIMPDH strain (AgIMPDH disrupted), was obtained following methodologies previously described (Jiménez et al 2005(Jiménez et al , 2008Ledesma-Amaro et al 2014b;Wendland et al 2000). Briefly, a replacement DNA cassette containing the kanMX4 selection module including the geneticin resistance (G418 r ) and flanked by specific homology regions was transformed into spores of the wild-type strain.…”
Section: Agimpdh Gene Disruption and Overexpressionmentioning
confidence: 99%
“…These strains lack both very long chain fatty acids and polyunsaturated fatty acids, which are undesired features in biodiesel blends. 26 Taking the above observations together, we propose A. gossypii as a novel and promising candidate for biolipid production that can offer an economically feasible alternative to some oleaginous yeasts. It has been demonstrated that modified strains of A. gossypii are able to accumulate high amounts of lipids and, additionally, it is possible to adapt the lipid profiles of such strains for them to become enriched in fatty acids of industrial relevance.…”
Section: Ashbya Gossypii As a Novel Organism For Microbial Oil Producmentioning
confidence: 91%
“…Accordingly, we have recently characterized both the elongase and desaturase systems of A. gossypii. 26 Additionally, metabolic engineering has also been applied to both the elongase and desaturase systems with a view to generating novel A. gossypii strains that are able to accumulate polyunsaturated fatty acids, monounsaturated fatty acids, lubricants or components of waxes. Likewise, A. gossypii strains with optimized features for the production of biodiesel have also been generated.…”
Section: Ashbya Gossypii As a Novel Organism For Microbial Oil Producmentioning
confidence: 99%
See 1 more Smart Citation